Neglected sulfur(vi) pharmacophores in drug discovery: exploration of novel chemical space by the interplay of drug design and method development (Dedicated to Professor Julius Rebek on the occasion of his 75th birthday.) - Lücking, U (Organic chemistry frontiers an international journal of organic chemistry, 2019)
Historically, sulfoximines, sulfondiimines and sulfonimidamides have been neglected pharmacophores in drug discovery even though they offer very interesting properties. This highlight shares the key learnings of various lead optimization approaches at Bayer AG that have successfully utilized these neglected sulfur(vi) functional groups to deliver multiple clinical candidates. In this context, the key synthetic methods utilized for the synthetic preparation of these unusual compounds will be outlined.